2015
DOI: 10.4103/0366-6999.160565
|View full text |Cite
|
Sign up to set email alerts
|

High Killips Class as a Predictor of New-onset Atrial Fibrillation Following Acute Myocardial Infarction

Abstract: Background:Recent observational studies have shown that patients with higher Killips score (>I) have higher risk of new-onset atrial fibrillation (NOAF) following acute myocardial infarction (AMI), while others drew a neutral conclusion. The ultimate predictive value of high Killips class on NOAF remained obscure.Methods:PubMed, Web of Science, China National Knowledge Infrastructure, and the Cochrane Controlled Trials Register Databases were searched until February 2015. Of the 3732 initially identified studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…NOAF is a common outcome in patients with AMI after PCI. In our present study, we found that 7.9% of patients experienced AF during hospitalization, and this is consistent with previous studies [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…NOAF is a common outcome in patients with AMI after PCI. In our present study, we found that 7.9% of patients experienced AF during hospitalization, and this is consistent with previous studies [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Killip grading is a simple clinical tool used to assess the severity of heart failure in patients with AMI. A meta-analysis indicated that a higher Killip class after AMI has a strong predictive value for NOAF [ 21 ]. In our study, we found that patients in the NOAF group had a higher Killip class, larger left atrium, and lower ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Binary logistic regression models were used to calculate the odds ratios (OR) and 95% confidence interval (CIs) for NOAF according to tertiles of PTFV1, LAD, and BNP, with the lowest tertile serving as the reference category. To account for potential confounding effects, we adjusted for known variables associated with NOAF or p value of <0.05 in the univariate logistic analyses including age, sex, estimated glomerular filtration rate(eGFR), smoking, drinking, hypertension(HTN), diabetes mellitus(DM), congestive heart failure (CHF), KILLIP>1, heart rate(HR) at admission, left ventricular ejection fraction(LVEF), prior myocardial infarction(MI), prior stroke, out-ofhospital cardiac arrest(OHCA), total cholesterol(TC), triglyceride(TG) and percutaneous coronary intervention(PCI) treatment [16][17][18]. Receiver operating characteristic (ROC) curve analysis was used to investigate the optimal cutoff values via the maximal Youden index (sensitivity+specificity-1).…”
Section: Discussionmentioning
confidence: 99%
“…Predictors of this arrhythmia was evaluated by several studies. [2][3][4] Shiyovich et al categorized new-onset AF as early and late. They reported the predictors according to this categorization.…”
mentioning
confidence: 99%